1998
DOI: 10.1074/jbc.273.49.32685
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Inactivating Mutations and pH-dependent Activity of Avian Sarcoma Virus Integrase

Abstract: Crystallographic studies of the catalytic core domain of avian sarcoma virus integrase (ASV IN) have provided the most detailed picture so far of the active site of this enzyme, which belongs to an important class of targets for designing drugs against AIDS. Recently, crystals of an inactive D64N mutant were obtained under conditions identical to those used for the native enzyme. Data were collected at different pH values and in the presence of divalent cations. Data were also collected at low pH for the cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
6
21
0
Order By: Relevance
“…Because this pH range coincides with the known pH vs activity assay profile for IN (22), there might be a direct relationship between the pH-dependent changes in the conformation of the active-site loop and the enzymatic activity of IN. As previously described (22), a change of protonation followed by a conformational change is observed in the core domain of native ASV IN for the Asp64 side chain around pH 6.2. Thus, we can see that pH-triggered structural changes of this protein are quite extensive, especially around its active site (Figure 3).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Because this pH range coincides with the known pH vs activity assay profile for IN (22), there might be a direct relationship between the pH-dependent changes in the conformation of the active-site loop and the enzymatic activity of IN. As previously described (22), a change of protonation followed by a conformational change is observed in the core domain of native ASV IN for the Asp64 side chain around pH 6.2. Thus, we can see that pH-triggered structural changes of this protein are quite extensive, especially around its active site (Figure 3).…”
Section: Discussionsupporting
confidence: 52%
“…Thus, we can see that pH-triggered structural changes of this protein are quite extensive, especially around its active site (Figure 3). Studies of enzymatic activity as a function of pH (22) indicated that the catalytic activity of ASV IN decreases dramatically at pH below 6.0. Therefore, it is very likely that some or all of the structural changes observed in the region of the active site are responsible for the changes in the enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, partial proteolysis experiments, deletion mutation results, and sequence similarity with other retroviral integrases, retrotransposons, and bacterial insertion elements suggest that there are three distinct domains in full-length ASV IN: the N-terminal, central core, and C-terminal domains (3). Structural analysis reveals that both the central core and C-terminal domains form dimers (9,10). All three domains have been implicated in the self-association of the full-length proteins.…”
mentioning
confidence: 99%
“…Though integrase has exo-and endonuclease activity [9][10][11][12][13][14][15][16][17][18], in spite of the recombinant full-length Eri15 protein that developed in the E. coli lacking part of the integrase core domain and DNA binding domain, endonuclease activity was discovered which could digest mtDNA (Fig. 3A).…”
Section: Characterization Of Reri15 Proteinmentioning
confidence: 99%